EFFECT OF A COMPOUND RECIPE (MEDICINAL PLANTS) ON SERUM INSULIN LEVELS OF ALLOXAN INDUCED DIABETIC RABBITS - Wadood, Noreen; Nisar, Muhammad; Rashid, Abdul; Wadood, Abdul; Nawab, Gul-; Khan, Ayub (Journal of Ayub Medical College Abbottabad, 2007)
Background: The present study was planned to observe the hypoglycaemic effect of the ’˜Compound recipe’ a combination of traditional medicinal plants in normal and alloxan induced diabetes mellitus. This study was performed to study the possible role of indigenous medicinal plants in the regeneration of pancreatic b- cells and in treatment of insulin dependent diabetes mellitus. Methods: The ’˜Compound recipe’ was administered daily in doses of 400-mg/kg body weight to normal and alloxan induced diabetic rabbits for a period of 4 months. The blood glucose and serum insulin levels were estimated before and 1, 2, 3 and 4 months after the administration of the extract. Results: The extract exerted a significant (P<0.05) hypoglycemic effect in alloxan diabetic rabbits. The hypoglycemic effect was not significant (P> 0.05) in normal rabbits. The extract exerted a significant (P<0.05) increase in insulin levels in alloxan diabetic rabbits. The effect on the insulin levels was not significant (P> 0.05) in normal rabbits. The doses used did not show acute toxicity or result in behavioral changes. Conclusion: From this study it may be concluded that the Compound recipe causes an increase in serum insulin levels in alloxan induced diabetic rabbits possibly due to regeneration of pancreatic b cells. Keywords : Compound recipe, hypoglycemic effect, alloxan-induced diabetes, serum insulin.